Upaya Pelestarian Musik Tradisional Lampung pada Generasi Muda di SMP Negeri 16 Bandar Lampung - Kartini Edison Simangunsong; Riyan Hidayatullah (Lembaga Pengembangan Kinerja Dosen, 2026)
This research examines the strategies and implementation of preserving traditional Lampung music at SMP Negeri 16 Bandar Lampung thru a descriptive qualitative approach. Data collection was conducted thru participatory observation, in-depth interviews with cultural arts teachers and students, as well as documentation studies. The findings reveal that preservation is carried out thru three pathways: (1) integration of traditional music material in cultural arts education, (2) organization of extracurricular activities based on Lampung instruments, and (3) collaboration with local artists and cultural figures. The main obstacles include the limited availability of instruments, the low initial motivation of students due to the influence of digital culture, and the lack of competence among teachers in the field of traditional music. Recommendations include the development of digital media-based learning methods, strengthening the local wisdom curriculum, and continuous training for cultural arts educators.